Challenging the Invisibility of Queer Young Mothers - Kuri, Erin (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
The social identity category of “young mothers” refers to a diverse and marginalized group, which has been socially constructed by dominant political and faith-based regimes in Western society. For youth who identify as queer young mothers, multiple vectors of oppression result in the erasure of their identity and material needs, contributing to reduced access to appropriate healthcare which impacts the quality of their health and wellness and the health and wellness of their children. In this article, I argue that although the visibility of queer pregnant and parenting youth is an important step in order to collectively establish particular material needs, that recognition alone is not enough. Collaborative advocacy efforts must take an intersectional approach. I place two texts into conversation with one another: Gayle Rubin’s essay titled Thinking Sex and Rebecca Trotzky-Sirr’s retrospective memoirstyle essay, titled The Revolutionary Artist Mom and Baby League: Putting Young Queer Parents on the Map, which centres the voices of youth who identify as queer young mothers. By placing these two texts together, political factors relating to both sexuality and gender, as well as age and economic status, are made apparent, allowing one to trace how and why this group is rendered invisible by communities that serve young mothers and by communities that support queer parents. I then discuss how the combination of these two texts establishes a clear need to collaboratively advocate with queer pregnant and parenting youth to ensure that their particular material needs are met. I explore an intersectional approach to advocacy, and I suggest a sense of direction with respect to advocacy efforts for the needs of youth who identify as queer young mothers. In support of my argument, I draw from feminist theory, contemporary motherhood studies, and queer studies.